Cultural impacts on shared decision-making: A cross-European study of psychiatrist preferences in 38 countries - Yasuhiro Kotera; Christopher Newby; Martina Rojnic Kuzman; Philip Gorwood; Andrea Fiorillo; Mike Slade (European Psychiatry)
Abstract